SOCIO-ECONOMIC PROFILE OF SCHEDULED TRIBES IN THE TEA GARDENS OF ALIPURDUAR DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
This paper is a part of research work on scheduled tribes in the tea gardens of Alipurduar district by Manik Paul under the supervision of Dr. Debasish Biswas to investigate into the socio-economic profile of the scheduled tribes (ST) population in the tea gardens (T.G.) of Alipurdar district in West Bengal. The demographic profile, religious beliefs, literacy, income, housing conditions and health conditions of scheduled tribes has been described in the selected tea gardens of Alipurduar district. The investigator tries to analyse the primary data of different socio-economic variables of scheduled tribes community in the tea gardens with the help of different tables and figures. It is observed that the ST population of male is higher than the female in the tea gardens area. It is found that in religious belief a large section of the tribal community got attracted to Christianity and converted to Christian. The majorities of the heads of the households are having education up to primary level only and they prefer nuclear family. The most of the tribal people are mainly engaged as labourer or tea garden workers and their income mostly depend on their self earnings. Most of the tribals have kacha houses and less have pucca houses. The tribal people in the tea gardens faced a miserable health conditions. The study indicates that more than 90% of the tribal people in the tea garden area have the habit of drinking of liquor. So the socio-economic conditions of scheduled tribes in the tea gardens area are very pathetic.